Papaya Seeds Membrane Peeling Machine - บุดดาจันทร์, กฤษฎากร; ภูวเกียรติกำจร, นิพนธ์ (YRU Journal of Science and Technology, 2018)
This research aims to design, build, and test papaya seed membrane peeling machines. This research contains three main parts, design of machine structures and 1/4 hp motor power engine, design membrane peeling machine using adjustable rectangle steel size 27x35x3 mm. drill a hole diameter 3 mm. and membrane peeling roller diameter 1/2 inches 18 cm long, covered with scotch brite. The test speed used was 200, 300, 500, 700 and 1350 rpm. The results showed that 82% is the maximum efficiency of quality to peel papaya seeds membrane using 500 rpm speed, with the performance to peel papaya seeds membrane at 10.06 kg/hour. The germination rate of the seeds that use this peeling machine is 80%.